Incidence and impact of postoperative atrial fibrillation after minimally invasive esophagectomy. Issue 6 (1st September 2016) - Day, R. W.; Jaroszewski, D.; Chang, Y.-H. H.; Ross, H. J.; Paripati, H.; Ashman, J. B.; Rule, W. G.; Harold, K. L.
Summary: Atrial fibrillation (AF) following open esophagectomy has been associated with increased rates of pulmonary and anastomotic complications, and mortality. This study seeks to evaluate effects of AF after minimally invasive esophagectomy (MIE). A retrospective review of patients consecutively treated with MIE for esophageal carcinoma, dysplasia. and benign disease from November 2006 to November 2011 was performed. One hundred twenty-one patients underwent MIE. Median age was 65 years (range 26–88) with 85% being male. Thirty-eight (31.4%) patients developed AF postoperatively. Of these 38 patients, 7 (18.4%) had known AF preoperatively. Patients with postoperative AF were significantly older than those without postoperative AF (68.7 vs. 62.8 years, P = 0.008) and more likely to be male (94.7% vs. 80.7%, P = 0.04). Neoadjuvant chemoradiation showed a trend toward increased risk of AF (73.7% vs 56.6%, P = 0.07). Sixty-day mortality was 2 of 38 (5.3%) in patients with AF and 4 of 83 (6.0%) in the no AF cohort ( P = 1.00). The group with AF had increased length of hospitalization (13.4 days vs. 10.6 days P = 0.02). No significant differences in rates of pneumonia (31.6% vs. 21.7% P = 0.24), stricture (13.2% vs. 26.5% P = 0.10), or leak requiring return to operating room (13.2% vs. 8.4% P = 0.51) were noted between groups. We did not find an increased rate of AF in our MIE cohort compared with prior reported rates in open esophagectomy populations. AF did result in an increased length of stay but was not a predictor of other short-term morbidities including anastomotic leak, pulmonary complications, stenosis, or 60-day mortality.